HUBUNGAN PERENCANAAN OLEH SEKRETARIS DPRD DENGAN EFEKTIVITAS KERJA PEGAWAI PADA SEKRETARIAT DPRD KABUPATEN CIREBON - Iskandar Zulkarnaen (Jurnal Ilmiah Publika, 2017)
ABSTRACT Research the authors do is about "Relationship Planning by Secretary of Parliament with Employee Effectiveness In Secretariat DPRD Cirebon". Based on observations made by researchers, the effectiveness of employees at the Secretariat DPRD Cirebon District Secretary of Parliament is still not achieved optimally. This can be seen from the indications are: Delays in handling reporting tools related to the problems handled and There is still a mistake in agenda or disposition of incoming aspirations. The above conditions are based on the researcher's assumptions one of them is because the Planning in the Secretariat of DPRD Cirebon Regency that has not run well, with indication that is: Scheduling scheduling activity not scheduled neatly causing delays in handling aspiration in either directly or written. The research method used by writer is by using survey method. Planning Dimensions include Forecasting, Goal Setting, Directing, Arranging Timelines, Expense budgeting, Developing Procedures, Establishing and Interpreting Wisdom. While the dimensions of Effectiveness are Time of work, Number of work, quality (quality) of work. Based on problem identification, the authors mengajuka hypothesis as follows: "There is a positive and significant relationship between Planning with Employee Effectiveness in Secretariat DPRD Cirebon". The hypothesis is as follows: Hᴏ (Hypothesis Zero): rs count <rs table there is no significant relationship between planning with effectiveness of employee work at Secretariat DPRD Kabupaten Cirebon Ha (Alternative hypothesis): rs arithmetic ≥ rs table there is a significant positive relationship between planning with effectiveness of employee work at the Secretariat DPRD Cirebon to test the hypothesis, the authors analyze by using Rank Spearman Correlation Coefficient. The results showed that the correlation between Planning with Employee Effectiveness based on Spearman Rank Correlation Coefficient calculation obtained rs value = 0.698 while rs table 0.317 with 95% confidence degree and error 5% and n = 39 thus the relationship is stated significant and the hypothesis that Researchers submit tested and acceptable.